(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Death is an inevitable part in life. Sudden or unexpected death is said to occur when a person not known to have been suffering from any dangerous disease, injury or poisoning is found dead or dies within 24 hours after the onset of terminal illness. In present study the postmortem examination were carried out and heart was dissected with inflow outflow methods of heart dissection and examined for gross changes in its structures, musculature, chambers, valves, coronary arteries. The heart was preserved in 10% formalin solution for histopathological examination. The histopathology reports received from pathology department was analyzed. Out of 182 cases of heart diseases studied 133 cases (73.08%) were male and 49 cases (26.92%) were female. Maximum 50 cases (27.45%) were observed in the age group 41-50 years. The atherosclerotic changes in coronary arteries were observed in 83 cases (45.59%). The signs of Ischemic heart disease were observed in 42 (23.08%) cases, The covering and layers of heart were affected in 19 cases (10.42%), the rarest condition pancarditis were observed in 1 case (0.55%). Left ventricular hypertrophy were seen in 16 cases (8.80%); replacement fibrosis in 10 cases (5.50%); hypertrophic obstructive cardiomyopathy (HOCM) were seen in 5 cases (2.74%) The involvement of valves of heart was observed in 3 cases (1.65%).